Penerapan Metode Demonstrasi Dalam Meningkatkan Hasil Belajar Pada Mata Pelajaran Fiqih Kelas Ii Di Mts Al-Mizan Putra Rangkasbitung Lebak - Pupu Mahpudin (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
The background of this research is that in Islam seeking knowledge is something that is obligatory for every human being because of the importance of knowledge to live life, one of the sciences in Islamic teachings is fiqh lessons. Fiqh science is the science that explains everything according to the teachings of Islam, both the procedures for worship or about how to socialise) between fellow creatures. Fiqh lessons are part of Islamic Religious Education, of course in their lessons teachers are required to be able to have the ability to develop teaching and learning systems creatively and imaginatively and master delivery methods that are able to motivate students, as well as a pleasant Teaching and Learning Activity process. This research was conducted with the aim of knowing; learning outcomes before and after using the demonstration method in fiqh subjects at MTs Al-Mizan putra, then to get data about the improvement of learning outcomes in fiqh subjects at MTs Al-Mizan putra Narimbang Rangkasbitung. The research method used is research with a qualitative design with a Classroom Action Research (PTK) approach. The Classroom Action Research (PTK) method in this study uses descriptive comparative studies and is presented in narrative form to make it easier for readers to understand the research results.The results of research in the field that the fiqh learning outcomes of class II A students before using the demonstration method were less than satisfactory, but after using the demonstration method, especially fiqh subjects, the learning outcomes of class II A students have increased. Data analysis from this study is that student learning outcomes have increased, namely; pre-cycle the number of students who are able to practice ablution properly is 65% or as many as 11 students, an increase was achieved in the first cycle test by 12% or 2 students so that the number of students who were able to practice ablution was 77% or as many as 13 students, an increase was also achieved in cycle II by 23% or 4 students, so that all students were able to perform ablution properly, namely 100% or as many as 17 students.